Cyber ​​Notary Problems in Legal Reform in Indonesia - Sujiati, Ani Eva (TABELLIUS: Journal of Law, 2024)
Cyber Notary is a concept of using digital technology that is expected to bring great benefits to the legal system and society in Indonesia. Along with the development of digital technology, this concept is proposed as a solution to improve efficiency and security in notary services. Cyber notary allows the process of document validation and electronic signing to be carried out online, utilizing technologies such as blockchain and digital signatures. However, its implementation still faces various challenges. One of the main problems is the lack of comprehensive and specific regulations governing the use of digital technology in notary practice. In addition, concerns about the security and privacy of electronic data are serious obstacles. Cyber attacks and the risk of electronic document forgery require a stronger and more sophisticated security mechanism. In addition, in remote areas that still experience limited internet access. The lack of understanding and technical expertise among notaries who are technologically literate also hinders the adoption of cyber notary. These factors emphasize the need for capacity building and training for notaries to adapt digital technology in cyber notary practices. This study uses normative legal research with a statute approach that examines regulations and laws relating to legal issues regarding cyber notary. This study examines the implementation and challenges faced in implementing the concept of "cyber notary" in Indonesia, noting the need for revision and development of more specific regulations and collaborative efforts between the government, technology providers, and notary associations to overcome these challenges. With the right steps, the implementation of cyber notary in Indonesia can increase efficiency and trust in notary services in the digital era.